Inwestycje turystyczne jako forma pobudzania popytu turystycznego na przykładzie gminy Głuchołazy - Puciato, Daniel (Tourist Investments As a Form of Tourist Demand Stimulation Based on Example of Głuchołazy Commune, 2008)
The increasing popularity of tourism results in its larger influence on GDP level of our country. Transformation processes and decentralisation caused high activity of regional self-governments in the stimulation of tourist economy development. The condition of tourist infrastructure is, besides tourist values and transport accessibility, the most important factor shaping tourist attractiveness of every town. To increase of tourist attractiveness, and consequently the demand for tourist services, suitably planned and realized investment policy every commune is essential. The Głuchołazy commune features many tourist values, however, it does not possess necessary tourist infrastructure. Such a situation is a reason for not sufficient utilization of the existing accommodation base and the seasonal character of tourist demand. In order to counteract this situation the commune planned a series of investments aiming to building the new and refurbishing the old infrastructure concentrated around the most popular place in the commune i.e. Biskupia Kopa. Further studies are necessary after the realization of planned investments in order to check their actual influence on tourist demand volume in the commune. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 118-128